Research on the Current Situation of Dance Education in the Context of Integrated Media—Taking Chinese Folk Dance as an Example - Nie, Kexin (Transactions on Social Science, Education and Humanities Research, 2024)
In 2020, the General Office of the Central Committee of the Communist Party of China and the General Office of the State Council issued the "Opinions on Comprehensively Strengthening and Improving School Aesthetic Education in the New Era". Dance education, as an important part of aesthetic education, has gradually received social attention. New media online communication methods such as short videos and live broadcasts are emerging. Traditional media such as television and radio are also constantly innovating. The development of integrated media is changing with each passing day. The theme of this article is research on the current situation of dance education under the background of integrated media - taking Chinese folk dance as an example. Through the research and analysis of relevant literature, combined with the limitations of integrated media itself, such as a single teaching model, imperfect teaching forms and methods, insufficient emotional integration, etc., as well as the unique dance culture of Chinese folk dance, this paper illustrates the current development of dance education Opportunities and challenges coexist, such as imperfect physical development, limited dance types, uneven content, lack of implementation, etc. Suggestions and thoughts are put forward for the future development of dance education, innovation is introduced, strict control is carried out, barriers are broken, and technology is empowered.